Total Neoadjuvant Therapy With Long-Course Radiotherapy Versus Chemoradiotherapy in High-Risk Locally Advanced Rectal Cancer (TNTCRT): A Multicenter, Randomized, Phase III Trial - Xin Wang; Yuanling Tang; Junyang Lu; Wenjian Meng; Ping Liu; Jitao Zhou; Feng Wen; Peirong Ding; Jun Li; Biao Wang; Qing Guo; Jian Qiu; et al. (Journal of Clinical Oncology, 2026)
PURPOSE High-risk locally advanced rectal cancer (LARC) carries a substantial risk of distant recurrence, which limits disease-free survival (DFS). We compared total neoadjuvant therapy (TNT) integrating long-course radiotherapy (LCRT) with uninterrupted doublet chemotherapy (doublet-LC TNT) versus conventional neoadjuvant chemoradiotherapy (nCRT). METHODS In this multicenter, randomized, phase III trial, patients with stage II/III LARC and at least 1 high-risk feature (cT4a-b, cN2, mesorectal fascia involvement, or cT3c-d with extramural vascular invasion) were enrolled. Patients were assigned to doublet-LC TNT (induction, concurrent, and consolidation capecitabine plus oxaliplatin with LCRT) before surgery or nCRT (capecitabine with LCRT) followed by surgery and adjuvant chemotherapy. The primary end point was DFS (ClinicalTrials.gov identifier: NCT03177382 ). RESULTS Between June 6, 2017, and December 27, 2023, 458 patients were randomly assigned to doublet-LC TNT (n = 232) or nCRT (n = 226). At a median follow-up of 51 months, doublet-LC TNT improved 3-year DFS (74.8% v 66.0%; hazard ratio [HR], 0.674 [95% CI, 0.489 to 0.929]; P = .016). Metastasis-free survival (MFS; 77.7% v 67.6%; HR, 0.655 [95% CI, 0.469 to 0.915]) and pathologic complete response rates (pCR; 26.37% v 9.80%; P < .001) were higher with doublet-LC TNT, whereas locoregional failure remained low and comparable (6.03% v 6.19%; P = .943). Although grade ≥3 adverse events during the neoadjuvant phase were more frequent with doublet-LC TNT (27.59% v 8.56%; P < .001), severe toxicities during the entire treatment course (28.02% v 24.32%; P = .371) and major postoperative complications (3.98% v 2.94%; P = .567) were comparable. CONCLUSION Compared with conventional nCRT, doublet-LC TNT improved DFS, MFS, and pCR rates with manageable toxicity. These findings support this intensified, doublet-based regimen as a standard option within the modern TNT paradigm. Further comparative studies are warranted to evaluate these results against other short-course radiotherapy‑based or nondoublet-concurrent TNT regimens.